What is the scientific evidence on Auriculotherapy and COVID-19? (Research, Society and Development, 2022)
This study aims to gather and analyze evidence on the use of Auriculotherapy during the COVID-19 pandemic. This is an integrative review, carried out in the PubMed, Scopus, Virtual Health Library (VHL), Web of Science and Science Direct databases with studies published until 11/06/2021. The Guideline Preferred Reporting Items for Systematic Reviews and Meta-Analyses - The PRISMA Statement was used. The research question was: What are the contributions/action of Auriculotherapy during the COVID-19 pandemic? A total of 16 studies were found, and after analysis, five studies were included in this work. Among the studies analyzed, 100% (n = 5) showed an improvement in the reduction of complaints treated and an improvement in the quality of health professionals assisted by Auriculotherapy. It was observed that Auriculotherapy proved to be effective in reducing anxiety, stress and depression, in addition to providing an improvement in professional performance and in the quality of sleep of these health professionals in times of the COVID-19 pandemic. The present study showed COVID-19 positive results regarding the use of Auriculotherapy. The therapy was effective in reducing anxiety, stress, depression, in addition to providing an improvement in the professional performance and quality of sleep of these health professionals, but future studies with a better level of evidence are needed to identify the results of use of auriculotherapy under the impacts caused by the pandemic.